The Simulation of Old Human Remains Detecting Utilizing Ground Penetrating Radar Image Processing - Jawad, Laith A.; Mahdi, Alaa S.; Mahmood, Faleh H. (Iraqi Journal of Science, 2023)
Many Iraqi provinces had collective cemeteries, especially in the middle and southern regions of Iraq, but many of those cemetery locations are undefined yet. Ground penetration radar has two features that make it optimal from a geophysical perspective for shallowly detecting sensitive materials near the surface. First, the instantaneous image is formed upon scanning, called a radargram. Second, the non-destructive inference of the scanned materials. For these two reasons, this technique was chosen to conduct a simulation process to reveal the old human remains in Iraq's central and southern areas using another model with the same physical feature (old burial) at the AL-Khamisiya site, Thi-Qar province.The demanded stages for completing the simulation process can be divided into two parts. The first part is that before the model's burial, a field survey was conducted to identify the site subsurface features and test the penetration extent of the selected antennas, in addition, to accurately calculating the speed of radar phase waves to obtain a calibrated measurement of the target's depth of burial. After the model's burying (the remains of old Iraqi humans), the second part included individual scanning and grouping at a depth of two m and four m.This simulation proved that the variation value in the dielectric constant between the burial medium (host medium) and the buried body (target) is the most critical determinant of detecting the remains' success or failure. Also, the work proved that low frequencies between (100-250) MHz are optimal for detecting human remains in a saline environment.